2021
DOI: 10.5812/aapm.115938
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nebulized Heparin on Weaning off Intubated Patients with Acute Respiratory Distress Syndrome (ARDS) Admitted to Intensive Care Unit (ICU): A Randomized Clinical Trial

Abstract: Background: Acute respiratory distress syndrome (ARDS) treatment is based on supportive care such as mechanical ventilation, prophylaxis of stress ulcer, prophylaxis of deep vein thrombosis (DVT), nutritional support, and treatment of underlying disease. Objectives: We aimed to investigate the effects of nebulized heparin on weaning off intubated ARDS patients admitted to the intensive care unit (ICU). Methods: In this double-blind clinical trial study, 60 patients with ARDS receiving routine care according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Meanwhile, among the two groups given normal saline and heparin, we did not discover a statistically significant difference in patient's time in the intensive medical unit. This discovery contradicts the findings that Olapour et al [ 26 ] reported. This discrepancy may have its root cause in the small sample size.…”
Section: Discussioncontrasting
confidence: 80%
“…Meanwhile, among the two groups given normal saline and heparin, we did not discover a statistically significant difference in patient's time in the intensive medical unit. This discovery contradicts the findings that Olapour et al [ 26 ] reported. This discrepancy may have its root cause in the small sample size.…”
Section: Discussioncontrasting
confidence: 80%
“…The characteristics of the included studies are summarized in Table 3 . 6 , 7 , 14 19 All studies were prospective randomized parallel-group controlled trials involving a total of 651 patients on mechanical ventilation (329 [intervention group] and 322 [control group]). A total of four of the eight studies were conducted in Australia and one each in Ireland, Iran, Netherlands, and Egypt.…”
Section: Resultsmentioning
confidence: 99%
“…Heparin may improve clinical outcomes by reducing fibrin deposition in the lungs, 20 and it also inhibits adhesion of bacteria and viruses on the respiratory surface, thereby, inhibiting their growth in the lungs. 17 , 20 However, the results of some studies showed no significant effect of inhaled heparin on the duration of ICU stay, which may be due to heterogeneity of the studies. The population of these studies mainly consisted of patients with airway burns, 18 , 21 while some were non-RCT studies, and their findings need further validation.…”
Section: Discussionmentioning
confidence: 99%
“…CVA is a vascular lesion that causes a neurological deficit and begins acutely and lasts over 24 hours (3). To diagnose CVA and find its causes and rule out other disorders similar to stroke, a number of evaluations such as electrocardiogram (ECG), computed tomography (CT) scan, magnetic resonance imaging (MRI), echocardiography, angiography, and Doppler sonography can be performed (4,5). In addition to causing death, strokes cause disability of the patient throughout life, which can be in the form of various movement, sensory, verbal, memory, visual, etc.…”
Section: Introductionmentioning
confidence: 99%